(untitled) (Research, Society and Development, 2021)
The school is the place where the student continues his formal education as individual, being capable of building his own values and concepts, and the scientific literacy in this matter takes on importance enabling the students the development of skills in addition to a critical e reflexive thinking. In this scope, this paper uses a qualitative approach of descriptive feature to detail the proposal of a didactic game called “De Olho no Velho Chico”, having as goal the development of scientific literacy in high school students – final years, throughout program content, vertebrate class – fish, starting from the relation “man x environment”, focusing in drawing attention to the current situation of the San Francisco river, more precisely, the area of the low San Francisco. The game facilitates the contact with the reality, being capable of associating the use of science with the daily life. It is important to point out that the game is still being tested to verify its feasibility as didactic resource capable of starting the process of scientific literacy of high school students – final years.